Assessment of endpoints in studies on peri-implantitis treatment: a systematic review - Faggion Junior, Clóvis Mariano; Listl, Stefan; Tu, Yu-Kang (Journal of dentistry, 2010)
Background - Endpoints are normally used to assess the efficacy of clinical treatment. In studies of peri-implantitis therapy, “true” endpoints are preferred to “surrogate”, because they can capture a substantial proportion of the effect of treatment on an outcome of interest, for example implant failure. - Objective - To assess the type of endpoints reported in the literature on peri-implantitis therapy, and their frequency of use. - Materials and methods - An extensive literature search was conducted (Pubmed, Cochrane, and Lilacs databases up to and including October 2009) to retrieve randomised controlled trials and non-randomised studies. Grey literature and major dental journals were also searched for potential studies. A variable was regarded as an endpoint only when it was clearly stated as the objective of an investigation. - Results - Fourteen studies are included in this review. Data on implant failure are presented solely as a consequence of peri-implantitis therapy, and not as an objective of an investigation. No true endpoint was described in any study on peri-implantitis. Mean pocket probing depth at implant, mean clinical attachment level at implant, and mean bleeding on probing (after pocket depth assessment) at implant were the three surrogate endpoints cited most often in the studies. More than 20 different clinical endpoints were described in the studies selected. - Conclusions - Reports did not reveal whether or not the therapy for peri-implantitis is useful for reducing the risk of implant failure. A consensus should be reached among dental researchers to standardise surrogate endpoints, and efforts should be made to validate these endpoints.
Gesehen am 07.02.2023